Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Lembaga Pembiayaan Ekspor Indonesia di Kantor Wilaya - Garibaldi Mirza N; Muhammad Asdar; Muhammad Ismail (Magister Management, Hasanuddin University, 2019)
This study aims to determine the effect of leadership style on employee performance with work motivation as an intervening variable in the Indonesian Export Financing Institution at the Makassar Regional Office. The population of this study were all employees of the Indonesian Export Financing Institution. The number of samples taken in this study were 50 respondents. The sampling method used in this study is the probability sampling method. Data collection in this study is to use archive strategies namely primary data and secondary data. Data were analyzed using multicollinearity and Path Analysis. The results of this study indicate that leadership style has a significant effect on work motivation. Leadership style also has a significant effect on employee performance. Work motivation significantly influences employee performance. Leadership style has a significant effect on employee performance through work motivation.